Always my grandpa a story for children about Alzheimer's disease - Scacco, Linda (Magination Press, 2006)
During a summer at his grandfather's house, young Daniel, with his mother's help, begins to understand Alzheimer's disease and how it affects not only Grandpa, but the entire family, as well.